Much ado about inequality - Mendoza, Ronald U (Archīum Ateneo, 2018)
Raul V. Fabella’s Capitalism and Inclusion under Weak Institutions is a compelling treatise on a wide range of economic development challenges faced by the Philippines. The Philippines’ national scientist in Economics does not disappoint with his latest book which lays out some of his candid thoughts on the policy options faced by the Philippines today. It is impossible to react to all the ideas in this book without putting together another full volume. Hence, I will focus this brief reaction on the conjointed issues of inequality and economic growth which the book revisits with provocative flair.